A Method for Determining the Mesh Stiffness of Internal Gear by Combining Finite Element Method and Contact Theory - Chang Lehao; Tian Hongwei; He Zhaoxia; Liu Geng (Jixie chuandong, 2018)
A method for determining the mesh stiffness of internal gears is proposed by using a combination of finite element method and the contact theory. The global deformation of contact point is separated by a full finite element model and a partial one. The local contact deformation is calculated by using the analytical formula for a line contact problem. The mesh stiffness and load distribution can be obtained after solving the nonlinear contact equilibrium equations. Compared with the conventional finite element method,the proposed method has higher computational efficiency and stability. And it also overcomes the disadvantage that the analytical method is difficult to consider helical gears and different gear ring structures. Then the influences of constraints number and thickness of ring gears on the mesh stiffness are analyzed. This method can provide effective guidance for the design of the strength and dynamic characteristics of the internal gears.